Characterisation of muscle calpain system SNPs and associations with production and beef quality traits in South African beef cattle following electrical stimulation and extended ageing - Webb, E.C. (Edward Cottington) (University of Pretoria, 2023)
Thesis (PhD (Animal Science))--University of Pretoria, 2023.